Pelatihan IELP Level 5 untuk Pilot - Triyani Retno Putri Sari Dewi; Widagdo, Rinosa Ari; Kurnianingsih, Lilis; Widyantoro, Arsanto Noorwahyu; Widodo, Dody Wahyu; Aviantara, Gema Firdaus (Politeknik Penerbangan Indonesia Curug, 2024)
This Community Service activity aims to improve pilots' English language skills through specialized training focused on ICAO English Language Proficiency (IELP) Level 5. The partners for this training are alumni from Politeknik Penerbangan Indonesia Curug, who are members of the Ikatan Pilot Alumni Curug (IPAC). Data from Politeknik Penerbangan Indonesia Curug indicates that only 15% of 505 IELP test participants in 2023 achieved Level 5, highlighting the need for enhanced proficiency to meet higher standards. The training was held on June 5, 2024, attended by 49 participants with 20 attending in person at Hotel Vega Gading Serpong and the rest joining virtually via Zoom Meeting. The session covered detailed explanations of IELP Level 5, common mistakes analysis, and IELP test simulations. It is expected that through this training, pilots will improve their proficiency and achieve IELP Level 5, ultimately contributing to better flight safety. The results of this training are anticipated to address gaps in pilots' English proficiency and support higher international flight safety standards.